Pengembangan Modul Stop Bullying untuk Meminimalisir Perilaku Bullying - Ilham Ba'iyattulhusna; Meilla Dwi Nurmala; Raudah Zaimah Dalimunthe (Lembaga Pengembangan Kinerja Dosen, 2025)
The purpose of this research is to produce a media in the form of a module so that students become more effective in learning about what bullying is. The module is created to assist guidance and counseling teachers in providing guidance and counseling services and to attract students' interest in learning about what bullying is so that they do not become perpetrators of bullying. This research uses the R&D (Research and Development) approach with the ADDIE development model, which consists of the steps: analyze (analysis phase), design (design phase), develop (development phase), implement (implementation phase), and evaluate. (tahap evaluasi). The data collection technique used in this study was conducted through the distribution of questionnaires to 170 students in the X grade at SMK Negeri 1 Malingping, resulting in 0% bullying in the high category, 5% bullying in the moderate category, and 95% bullying in the low category. Then, from the results of the questionnaire distribution, the findings were compiled into a product in the form of a module and the product's validity was tested by several experts, namely content experts, media experts, language experts, and practitioner experts. The product trial was conducted through a service with reference to the pretest and post-test results carried out on 8 students in the moderate bullying category. The 8 samples received scores from the test results using the Wilcoxon matched pairs test, and it was found that all 8 samples were in the negative ranks, meaning these 8 students experienced a decrease in pretest to post-test scores. This indicates that the 8 samples experienced a reduction in bullying behavior with an average score of 4.50 and a sum of ranks of 36.00. Additionally, the results from the statistical table of the Wilcoxon matched pairs test showed an Asymp. Sig. (2-tailed) value of 0.012. Referring to the hypothesis decision-making process, the value of 0.012 is lower than 0.05, indicating that the hypothesis is accepted, meaning the stop bullying module can be considered effective for implementation to students.